2020
DOI: 10.5902/2236583442752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência De Dor Crônica Em Acadêmicos De Uma Instituição De Ensino Superior Privada

Abstract: Objetivo: Descrever a prevalência e fatores relacionados a dor crônica em universitários da área da saúde de uma instituição privada de ensino superior. Métodos: estudo descritivo transversal com acadêmicos de ambos os sexos, dos cursos da saúde de uma universidade privada, localizada na cidade de Feira de Santana/BA. Todos os participantes foram submetidos a um questionário para coleta de dados sociodemográfica e o Pain Detect Questionaire, para identificar indivíduos com dor crônica. Este estudo foi aprovado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…However, there are few studies conducted with university students as the target public. 1,4,13 Through this research, we observed a frequency of female participation of 80% of the total sample, corroborating the research of Gomes-Neto; Sampaio; Santos, 14 where 200 university students in the health area participated in the study, with 81% being female.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, there are few studies conducted with university students as the target public. 1,4,13 Through this research, we observed a frequency of female participation of 80% of the total sample, corroborating the research of Gomes-Neto; Sampaio; Santos, 14 where 200 university students in the health area participated in the study, with 81% being female.…”
Section: Discussionsupporting
confidence: 87%
“…In theory, people with a higher level of education should present a greater capacity for pain self-management and, consequently, less chronification of their symptoms. 13 Regarding chronic low back pain, 62% of university students reported having chronic low back pain, and 58% reinforced having felt it during the last week, being this more frequent in students in their last year (54%). This fact was also found in the study by Morais; Silva; Silva, 21 who evaluated 410 physical therapy students about the factors associated with low back pain and obtained a result that the prevalence of low back pain in the last year was 56.3% (95%CI:51.5-61.2), and in the last week it was 27.1% (95%CI: 22.8-31.4).…”
Section: Discussionmentioning
confidence: 99%